(untitled) (INNOVATIVE ECONOMY, 2025)
Savitskyi A.V. ASSESSMENT OF THE IMPACT OF USA TARIFF POLICY CHANGES ON FOREIGN ECONOMIC ACTIVITY OF DOMESTIC ENTITIES Purpose. The aim of this research is to form an approach for assessing the impact of USA tariff policy changes on the global level; to identify the key macroeconomic factors that cause threats for economic systems and its entities functioning; to substantiate individual aspects of production management and further sales processes under conditions of global trade instability. Methodology of research. In the process of research, methods of statistical and dynamic analysis of export-import operations indicators have been used, both in global, regional and macroeconomics dimensions. In order to establish and substantiate the impact of USA tariff policy changes on individual economic entities, it was taken into consideration methods of grouping and systematizing the problems of foreign economic activities and the postulates of absolute and relative advantages of international trade theories. Findings. Based on a statistical and dynamic analysis of the indicators of USA export-import operations in the world and in relation to European Union and Ukraine, the main trends for interdependence of domestic export from the developing situation at the international markets were identified. This allowed to group and substantiates the macroeconomics factors that cause threats for economic systems and its functioning both for developed and developing countries on the national and global levels. Subsequently, within global and regional dimensions, an analysis of Ukraine’s export-import operations in relation to other countries of the world was carried out, that made possible to identify its further guidelines and establish a trajectory for foreign trade relations development. Originality. The originality of made research deals with application of comprehensive approach to the analysis of international trade indicators through substantiation of individual macroeconomics factors of influence, which allows to identify the weaknesses and strengths of domestic enterprisers’ export capacity making in order to adapt to new market conditions caused by the imbalance of global tariff policy. Practical value. The application of the presented approach, for managers of export-oriented enterprises, allows to establish further priorities for conducting foreign trade operations and understanding in which markets it is possible to maintain, strengthen or form export potential, reduce the costs of business processes and find alternative suppliers of raw materials. Key words: tariff policy, tariff rates, export, import, international trade, macroeconomics factors, national level, global level.